(untitled) - Isida, Ryuziro (Tokyo, 1969)
This book introduce about territory related with history and geography, physical setting, land forms, climate. Population and settlements, resources and industries, socio-economic reality
Keywords: Nhật Bản,Japan; Địa lý,Geography